O zasadności zmian zakresu penalizacji przestępstwa propagowania faszyzmu i totalitaryzmu - Muszyńska, Anna; Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In the rich literature on the subject, the discussion about criminal liability for the offence under Article 256 of the Penal Code concerning the propagation of fascism and totalitarianism remains relevant, especially when one observes an increased level of activity and threat from radical nationalist movements, or the emergence of authoritarian, and even totalitarian, methods of exercising power. The mentioned issue engages significant attention from scholars and practitioners in the judicial field. The frequent contestation of the regulation specified in Article 256 of the Penal Code is associated with difficulties in defining the scope of criminalization, as well as the correct interpretation of the elements of the offence. Similarly, the legislative efforts undertaken by the legislator as of October 1, 2023, aimed at clarifying the elements illustrating the prohibited act did not achieve the desired result; instead, they garnered criticism and deepened the previously existing ambiguities. In the outlined situation, the authors of the present article join the ongoing discussion about the normative approach to the offence under Article 256 of the Penal Code and seek an optimal solution in this regard. This work aims to assess the amended regulation, verify interpretational doubts, and attempts to formulate de lege ferenda proposals without reproducing the shortcomings of the approach that is currently prevalent. The considerations based on the formal-dogmatic and theoretical-legal methods are accompanied by references to earlier solutions regarding this type of offence. These references highlight the path of changes marked by numerous legal and practical problems. The authors point out flaws in previous solutions and critically address situations where responsibility for the prohibited act is determined based on judicial interpretation, seeking out issues that the legislator did not explicitly include. They also point out the need for legislative intervention in the currently amended approach to the offence, expanding the scope of penalization and relying on sufficiently vague elements, allowing for varied interpretations. The authors contemplate the conclusions that can be drawn from past experiences, including the use of ambiguous elements that require scholarly analysis and the dangers associated with criminalizing not only the promotion of a totalitarian system but also the extreme doctrines and ideologies linked to it. In conclusion, the authors approach rational proposals with understanding, recognizing that transforming the content of Article 256 of the Penal Code and proposing a new form of the offence will not be without normative shortcomings. On the other hand, opting for a radically different solution, such as abandoning criminalization, is currently not justified and accepted.
Keywords: crime; totalitarianism; Nazism; propagation of fascism; totalitarian regime; totalitarian ideologies; fascist symbols